A case study of Turkish and Polish English teachers' effectiveness - Bavlı, Bünyamin (My University, 2017)
The study intends to explore factors influencing the perceptions of English language teachers' effectiveness and effectiveness perceptions of English language teachers in Turkey and Poland. To explore background phenomenon, qualitative methodology, and especially holistic multiple-case designs were employed in the study. The study was conducted in two public upper-secondary schools located in a city in the center of the Poland and two public upper-secondary schools located in the central Marmara region of Turkey. The participants of the study were comprised of 12 English language teachers and 35 students in Poland, and 12 English language teachers and 61 students in Turkey. Study data were primary obtained through individual interviews with teachers, focus group interviews with students and passive-participant observation by classroom observation forms generated by the researcher. Study findings were categorized into two areas: factors influencing effectiveness perceptions of English language teachers in Poland and Turkey and perceptions of teachers and students about teacher effectiveness in these countries. Findings revealed that effectiveness perceptions of English language teachers in Poland and Turkey were influenced by identical categories, namely factors related to teacher education, personal and social factors, instructional factors, and contextual factors. However, when subcategories were examined, it was obvious that factors vary. With reference to the first category, factors related to teacher education, factors related to pre-service education and in-service teacher education influenced effectiveness perceptions of English language teachers in Poland and Turkey. Another category influencing effectiveness perceptions of English language teachers in Poland and Turkey was personal and social factors originated of learners and parents. In addition to the factors such as teacher education and personal and social factors, instructional factors also influenced the perceptions of English language teachers' effectiveness in Poland and Turkey. Teachers and students in both countries stated that curriculum-related factors influenced effectiveness perceptions of English language teachers. Besides factors such as teacher education, personal and social factors and instructional factors, contextual factors such as learning environments consisting of students with mixed ability, overcrowded classrooms, inspection and evaluation, salary, double-shift schooling, teacher promotion, administrative tasks, teacher collaboration, employment of substitute teaching staff, learning experiences and conditions in previous grade and school such as lack of English teachers, teaching methods employed and elective courses, and finally high mobility or frequent change of teachers all had an impact on effectiveness perceptions of English language teachers' in Poland and Turkey. Effectiveness perceptions of English language teachers in Poland and Turkey were categorized under four main categories: effectiveness perceptions about classroom management, effectiveness perceptions about classroom using instructional strategies, effectiveness perceptions about employing teaching materials, and effectiveness perceptions about assessment and evaluation. Effectiveness perceptions about classroom management comprised of allocation sufficient time for each person during instruction, defining classroom rules, collaborating with students to define classroom rules, providing positive reinforcement for students, motivating students to respond, allowing students to explain learning difficulties and employing various seating arrangements. Effectiveness perceptions about using instructional strategies involved employing a variety of group strategies, employing pair work, employing communicative practice, employing authentic practice, and using English as a medium of instruction during instruction. Effectiveness perceptions about employing teaching materials consisted of using authentic teaching materials, developing one's own materials, using online teaching sources or applications, using visuals, and motivating students to use dictionaries. Finally effectiveness perceptions about assessment and evaluation included providing feedback (oral or written) for homework assignments, using online homework, making formative assessment, making summative assessment, providing oral and written feedback following the assessment, and re-teaching following assessments.

Bu çalışma Polonya ve Türkiye’deki İngilizce Öğretmenlerinin etkililiklerini etkileyen faktörleri ve öğretmen etkililik algılarını belirlemeyi amaçlamaktadır. Çalışmada arka plandaki olguyu keşfetmek amacıyla nitel araştırma yöntemlerinden bütüncül çoklu durum deseni kullanılmıştır. Araştırma Polonya ülke merkezinde yer alan bir şehirde iki devlet lisesinde ve Türkiye’de ise Marmara bölge merkezinde yer alan iki devlet lisesinde yürütülmüştür. Çalışmanın katılımcılarını Polonya’da 12 İngilizce öğretmeni ve 35 öğrenci, Türkiye’den 12 İngilizce öğretmeni ve 61 öğrenci oluşturmaktadır. Araştırma verileri esas olarak öğretmenlerle gerçekleştirilen bireysel görüşmeler, öğrenciler ile gerçekleştirilen odak grup görüşmeleri ve araştırmacı tarafından geliştirilen gözlem formları aracılığı ile toplanmıştır. Araştırma bulguları iki boyut altında ele alınmıştır: Polonya ve Türkiye’deki İngilizce öğretmenlerin etkililik algılarını etkileyen faktörler ve İngilizce öğretmeni ve öğrencilerin öğretmen etkililiklerine yönelik algıları. Elde edilen veriler Polonya ve Türkiye’deki İngilizce öğretmenlerinin etkililik algılarının öğretmen eğitimi, bireysel ve sosyal faktörler, öğretimsel faktörler ve bağlamsal faktörler gibi benzer faktörlerden etkilendiğini ortaya çıkarmıştır. Ancak, alt kategoriler incelendiğinde, faktörlerin farklılık gösterdiği belirlenmiştir. İlk kategoriyle ilgili olarak, öğretmen eğitimi, hizmet öncesi ve hizmet içi eğitimle ilgili faktörlerin öğretmenlerin etkililik algılarını etkilediği görülmüştür. Polonya ve Türkiye’de İngilizce öğretmenlerinin etkililik algılarını etkileyen diğer bir faktör ise esasen öğrenen ve velilerle ilgili olan bireysel ve sosyal faktörlerdir. Bununla birlikte, öğretmen eğitimi, bireysel ve sosyal faktörlerin yanı sıra öğretimle ilgili faktörler de İngilizce öğretmenlerinin etkililik algılarını etkileyen faktörler arasında yer almaktadır. Her iki ülkeden elde edilen veriler eğitim programıyla ilgili faktörlerin İngilizce öğretmenlerinin etkililik algılarını etkilediklerini ifade etmişlerdir. Öğretmen eğitimi, bireysel ve sosyal faktörler, öğretimle ilgili faktörlerin yanında karma becerilere sahip öğrenciler, kalabalık sınıflar, teftiş ve değerlendirme, maaş, ikili öğretim, kariyer sistemi, idari görevler, öğretmen iş birliği, ücretli öğretmen istihdamı, bir önceki öğrenim kademesindeki öğrenme yaşantıları ve şartları, az sayıdaki İngilizce öğretmeni, kullanılan öğretim yöntemleri, seçmeli dersler, yüksek düzeyde öğretmen değişimi ya da hareketliliği gibi bağlamsal faktörler de İngilizce öğretmenlerinin etkililik algılarını etkileyen faktörler arasında yer almaktadır. Polonya ve Türkiye’deki İngilizce öğretmenlerinin etkililiklerine yönelik algıları dört ana başlık altında ele alınmıştır: sınıf yönetimine yönelik etkililik algıları, öğretim stratejileri kullanımına yönelik etkililik algıları, öğretim materyali kullanımına yönelik etkililik algıları, ve ölçme değerlendirmeye yönelik etkililik algılarıdır. Sınıf yönetimine yönelik etkililik algıları, öğretim sürecinde her bireye yeterli zaman ayırma, sınıf kuralları belirleme, sınıf kuralları belirlemede öğrencilerle işbirliği yapma, öğrencilere olumlu dönüt sağlama, öğrencileri geri cevap vermede (yanıtlama) motive etmek, öğrenmelere öğrenme güçlüklerini ifade etmeye izin verme, öğretim sürecinde çeşitli oturma düzeni kullanmayı kapsamaktadır. Öğretim stratejileri kullanımına yönelik etkililik algıları, çeşitli grup stratejileri kullanma, ikili çalışma teknikleri kullanma, iletişime yönelik uygulamalar yaptırma, otantik uygulamalar yaptırma, İngilizceyi öğretim dili olarak kullanmayı amaçlamaktadır. Öğretim materyali kullanımına yönelik etkililik algıları otantik araç gereç kullanma, kendi öğretim materyallerini geliştirme, online (çevrim içi) öğretim kaynakları ve uygulamaları kullanma, görseller kullanma ve öğrencileri sözlük kullanmaya teşvik etmeyi içermektedir. Son olarak, ölçme değerlendirmeye yönelik etkililik algıları ev ödevlerine dönüt verme (sözlü ve yazılı), online (çevrim içi) ev ödevi verme, formatif değerlendirme yapma, sumatif değerlendirme yapma, değerlendirme sonrası sözlü ve yazılı dönüt sağlama, değerlendirme sonrası gerektiğinde yeniden öğretim yapma faaliyetlerini kapsamaktadır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2017
Keywords: Factors; Perceptions; Teacher effectiveness; Faktörler; Algılar; Öğretmen etkililiği